THE INFLUENCE OF APPLYING PROBLEM BASED LEARNING BASED ON SOFT SKILL TO INCREASE STUDENTSâ CREATIVITY IN THE SUBJECT DEVELOPMENT OF HIGH SCHOOL MATHEMATICS CURRICULUM - Murni, Atma; Dian Anggraini, Rini (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The objective of this research was to find out the influence of applying problem based learning based on soft skills toward increasing studentsâ creativity in the subject Development of High School Mathematics Curriculum (DHSMC). The method used in this research was Pre-experimental method with the Intec-group comparison design. It was applied to the students who took DHSMC subject in the even semester of the year 2013/2014 for two classes. There were 28 students in the experimental class, who treated by using Problem Based Learning on Based Soft Skills and 25 students in the control group which were taught by using Problem Based Learning. The data of studentsâ creativity was collected by using questionnaires by Likert Scale, observation, and interview. The aspects of creativity involved flexibility, originality, elaboration, and fluency. The data obtained was normal distributed and has homogen variance. As a result, the data was analyzed through the comparative independent sample that was t-test. The result of the research showed that there was not influence on studentsâ creativities after teaching by problem based learning based on soft skills and those by problem based learning in taking DHCMC subject.Key words: soft skills, problem based learning, creativity